Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.clinph.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Resting cranial and upper cervical muscle activity is increased in patients with migraine

Abstract: This provides preliminary evidence to date of possible cranial muscle involvement in migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It has previously been suggested that increased muscle tension could be secondary to inflammation that acts via muscle spindles in muscle pain syndromes (38,39) or due to increased muscle nociception in tension type headaches (40). Neck muscle tension has previously been examined in migraine patients with EMG (41)(42)(43)(44)(45)(46)(47). Findings suggest that EMG activity is increased interictally in the cranial and upper cervical muscles during rest (41) and stressful mental tasks (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been suggested that increased muscle tension could be secondary to inflammation that acts via muscle spindles in muscle pain syndromes (38,39) or due to increased muscle nociception in tension type headaches (40). Neck muscle tension has previously been examined in migraine patients with EMG (41)(42)(43)(44)(45)(46)(47). Findings suggest that EMG activity is increased interictally in the cranial and upper cervical muscles during rest (41) and stressful mental tasks (42).…”
Section: Discussionmentioning
confidence: 99%
“…Neck muscle tension has previously been examined in migraine patients with EMG (41)(42)(43)(44)(45)(46)(47). Findings suggest that EMG activity is increased interictally in the cranial and upper cervical muscles during rest (41) and stressful mental tasks (42). Studies have also reported increased activity in the extensors of migraine patients during neck flexion (43,44), and increased activity compared to the generated force (45).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as RELAX-Jr was assessed using a typically developing sample of children, its cleaning performance in clinical samples (e.g., autism, attention deficit hyperactivity disorder, epilepsy) remains to be established. We also note that lower density recordings, particularly those with <32 electrodes, could achieve significantly poorer performance resulting from insufficient ICA decomposition, which may not adequately separate neural from artifactual components (Janani et al, 2018;Klug & Gramann, 2021). For such recordings, the use of non-ICA based methods for data pre-processing should be considered.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%